2021
DOI: 10.1039/d1ta06978k
|View full text |Cite
|
Sign up to set email alerts
|

High-precision, stretchable kirigami-capacitive sensor with ultra-low cross-sensitivity for body temperature monitoring

Abstract: Wearable temperature sensors meeting the resolution of medical-grade thermometers are needed to continuously monitor skin temperature variations indicative of diseases and sports performance. Herein, we present a new technique for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 56 publications
0
25
0
Order By: Relevance
“…The stiffness (or softness) of conductive nanocomposites can be designed to match human skin or other biological tissues, enabling the sensors to be comfortably worn directly on skin for accurate real-time monitoring of body temperature. By designing the material combination and sensors’ geometry, the detection limits and thermal conductivity can be engineered to provide precise and accurate monitoring of body temperature …”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stiffness (or softness) of conductive nanocomposites can be designed to match human skin or other biological tissues, enabling the sensors to be comfortably worn directly on skin for accurate real-time monitoring of body temperature. By designing the material combination and sensors’ geometry, the detection limits and thermal conductivity can be engineered to provide precise and accurate monitoring of body temperature …”
Section: Applicationsmentioning
confidence: 99%
“…By designing the material combination and sensors' geometry, the detection limits and thermal conductivity can be engineered to provide precise and accurate monitoring of body temperature. 141 Although the electrical conductivity of stretchable conductive nanocomposites is intrinsically sensitive to temperature, their temperature sensitivity is typically low. By controlling the microcrack density and geometry in conductive nanocomposites, the temperature sensitivity of wearable sensors, which is given by k T = ΔR/(R 0 ΔT), can be enhanced significantly.…”
Section: Applicationsmentioning
confidence: 99%
“…From Figure d, the Δ C / C 0 value of the sensor is stepwise increased as the temperature is stepwise increased by 0.02 °C and then approaches a platform when the temperature is fixed at a constant. The monitoring accuracy of our sensor is as low as 0.02 °C, which is more accurate than all previously reported temperature sensors. ,, , …”
Section: Resultsmentioning
confidence: 55%
“…It is found that the sensor temperature sensitivity is ca. 25.99% °C –1 , which is higher than those of previous capacitive temperature sensors or resistance temperature sensors. A cyclic heating–cooling test of this sensor within 30–40 °C is implemented as described in Figure b. It is observed that the Δ C / C 0 value of the sensor is increased with increasing temperature and then is decreased instantly with decreasing temperature.…”
Section: Resultsmentioning
confidence: 95%
“…[ 40 ] However, the TPU‐based capacitive sensor still shows high sensitivity to pressure even though its pressure sensitivity was relatively small at 0.038 kPa −1 . [ 41,42 ] The temperature resolution of the sensor degraded to 5.4 °C when the sensor was subjected to pressure as low as 1 kPa, [ 40 ] which is much lower than the pressure (2.7–4.0 kPa) employed by typical medical compression garments. [ 43 ]…”
Section: Introductionmentioning
confidence: 99%